Extraction, Characterization, and Encapsulation of Cinnamon Hydrosol Obtained via Microwave-Assisted Hydrodistillation: Analysis of Antioxidant and Antimicrobial Activities - Bruno Estela; Campañone Laura Analía (Bioactivities, 2024)
Microwave-assisted hydrodistillation (MAHD) method was employed to extract cinnamon oil and hydrosol (a byproduct). The total polyphenol content (TPC) of the cinnamon hydrosol (CH) was determined using the Folin-Ciocalteu method, and its antioxidant power was assessed through the DPPH radical reduction method. Gas chromatography was utilized to quantify the main bioactive compound (cinnamaldehyde). The disc agar diffusion method was applied to evaluate the inhibition of pathogenic microorganisms. To protect the bioactive compound, an encapsulation method involving cross-linking with calcium alginate was utilized. The capsules were examined using environmental scanning electron microscopy (ESEM). The TPC content was found to be 15.63 ± 0.21 mg gallic acid/g dry matter, and the DPPH radical inhibition rate was 84.26 ± 1.35%. CH exhibited a significant inhibitory effect against Escherichia coli, and a moderate inhibition effect against Shigella flexneri, Salmonella spp., Salmonella typhimurium, and Escherichia coli EPEC. Finally, successful encapsulation of CH was achieved using sodium alginate, resulting in bead sizes ranging between 1.75 and 2.75 mm.